Karakteristik Kawasan Alam Sutera, Tangerang Selatan - Andre Pratama; Muhammar Khamdevi (Advances in Civil Engineering and Sustainable Architecture, 2024)
Alam Sutera is planned with a one-stop living and green city approach, which is good, safe, comfortable, and healthy. This approach tries to differentiate it from the surrounding and other formal areas. This study tries to examine and identify the characteristics of the Alam Sutera area by analyzing these characteristics using urban theories. This research uses a qualitative approach with a case study approach to produce data, which will then be used in developing hypotheses. The research results show that the planning for Alam Sutera has good and complete urban elements, but the local context issues (environment and culture) have not been properly considered. Alam Sutera is the same as the surrounding formal areas except in terms of greening, but it does not yet have a distinct and different local identity.